Blue hydrogel and preparation method and application thereof

CN122978346APending Publication Date: 2026-10-27OCEAN UNIV OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611092832.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]目前为止,未有关于可以用于日用洗护清洁产品中作为增稠剂或悬浮剂的具有较高的粘度和透光率的聚丙烯酸类的蓝色水凝胶及制备方法的报道

Benefits of technology

[0035]本发明的蓝色水凝胶具有较高的粘度和透光率,其未额外添加色素而呈现出蓝色色调。其在不同的pH值下粘度和透光率有所不同,可以根据实际需要调节。本发明的蓝色水凝胶可以作为增稠剂或悬浮剂用于日用洗护清洁产品,由于水凝胶本身具有漂亮的蓝色,有利于遮盖原料杂色,让成品色泽均匀,有利于降低配方成本,减少额外色素添加量;在生产投料时,由于增稠剂或悬浮剂自带颜色,则在搅拌过程中,可以直接观察结块、未溶部分,可以辅助判断溶解、分散状态,提高生产便利性。本发明的制备方法可以得到粘度和透光率均较高的蓝色水凝胶。本发明的制备方法条件温和,有利于推广应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978346A_ABST
    Figure CN122978346A_ABST
Patent Text Reader

Abstract

The application discloses a kind of blue hydrogel and preparation method and application, the blue hydrogel is not added pigment extra;It is prepared from the following raw materials: acrylic monomer, acrylic C1-C4 ester, trimethylolpropane triacrylate and N, N-methylene bisacrylamide;Wherein, the mass of acrylic C1-C4 ester, the mass of acrylic monomer and the sum of the mass of trimethylolpropane triacrylate and N, N-methylene bisacrylamide are 145~160:90~110:1;The mass ratio of trimethylolpropane triacrylate and N, N-methylene bisacrylamide is 1:0.8~1.The blue hydrogel is blue without additional pigment, and can be used as thickening agent or suspending agent in daily cleaning products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of emulsion thickeners, specifically relating to a blue hydrogel, its preparation method, and its application. Background Technology

[0002] Traditional powdered carbomer thickeners face significant challenges in practical applications: their dissolution process is complex, requiring high-speed shearing and slow feeding, and they are prone to forming insoluble "fish-eye" clumps due to uneven wetting; the lightweight powder easily generates dust, causing both raw material loss and impacting the production environment; at the same time, subtle differences in the dissolution process directly affect the viscosity and transparency of the final product, making it difficult to guarantee batch stability and severely restricting production efficiency and product consistency.

[0003] Most daily cleaning and personal care products (including shampoo, hand soap, shower gel, etc.) contain thickeners or suspending agents. This makes the system stable during storage, easy to control when pouring, and less prone to spillage.

[0004] Using polyacrylic acid emulsions or their gels as thickeners can avoid the problems associated with traditional powdered carbomer thickeners. Literature reports a polyacrylic acid emulsion thickener, gel, and preparation method. This polyacrylic acid emulsion is prepared from benzophenone, acid monomers, and acrylate monomers with hydrophobic long side chains. However, this preparation method uses benzophenone as a raw material. Benzophenone has certain genotoxicity and estrogenic effects; long-term skin contact may cause contact dermatitis, photosensitivity reactions, etc.

[0005] In addition, if the thickeners or suspending agents added to daily washing and cleaning products are colored, especially if they are beautiful colors, the formulation cost can be reduced, the amount of additional pigments can be reduced, the impurities in the raw materials can be covered, and the finished product can have a uniform color. When feeding materials during production, since the thickeners or suspending agents are colored, the lumps and undissolved parts can be directly observed during the stirring process, which can help judge the dissolution and dispersion state and improve the convenience of production.

[0006] To date, there are no reports on blue polyacrylic acid hydrogels with high viscosity and light transmittance that can be used as thickeners or suspending agents in daily washing and cleaning products, nor on their preparation methods. Summary of the Invention

[0007] In view of this, one object of the present invention is to provide a blue hydrogel that exhibits a blue hue without the addition of additional pigments, has high viscosity, and a light transmittance greater than 70%, and can be used as a thickener or suspending agent in daily washing and cleaning products. Another object of the present invention is to provide a method for preparing the aforementioned blue hydrogel. A further object of the present invention is to provide an application of the blue hydrogel as a thickener or suspending agent in daily washing and cleaning products.

[0008] The present invention achieves the above objectives using the following technical solutions.

[0009] On the one hand, the present invention provides a blue hydrogel without additional pigments, with a light transmittance of more than 70% and a transparent or semi-transparent appearance; in its viscosity-pH value relationship curve, in the pH value range of 7.5 to 10, its viscosity gradually increases with the increase of pH value, and in the pH value range of 10 to 11, its viscosity gradually decreases with the increase of pH value. It is prepared from raw materials including: acrylic monomers, C1-C4 acrylates, trimethylolpropane triacrylate and N,N-methylenebisacrylamide; The mass ratio of C1-C4 acrylate, acrylic monomers, and the sum of the masses of trimethylolpropane triacrylate and N,N-methylenebisacrylamide is 145-160:90-110:1; the mass ratio of trimethylolpropane triacrylate to N,N-methylenebisacrylamide is 1:0.8-1. The acrylic monomers are selected from one or more of acrylic acid and methacrylic acid; the C1-C4 acrylates are selected from one or more of methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, and tert-butyl acrylate. This hydrogel exhibits a blue hue without the need for additional pigments and possesses high viscosity and light transmittance. It can be used as a thickener or suspending agent in daily cleaning and personal care products, effectively masking impurities from other raw materials and reducing the amount of pigment required. Furthermore, it aids in determining the dissolution and dispersion states during production, improving manufacturing convenience.

[0010] In some embodiments, the blue hydrogel is prepared from raw materials including: acrylic monomers, C1-C4 acrylates, trimethylolpropane triacrylate, N,N-methylenebisacrylamide, emulsifiers, initiators, water, and alkali.

[0011] In some specific embodiments, the blue hydrogel is prepared from raw materials including: acrylic acid, C1-C4 acrylate, trimethylolpropane triacrylate, N,N-methylenebisacrylamide, emulsifier, initiator, water, and alkali.

[0012] In this invention, the emulsifier forms an aqueous emulsifier solution during use, including a first aqueous emulsifier solution and a second aqueous emulsifier solution. The emulsifiers in the first aqueous emulsifier solution and the second aqueous emulsifier solution may be the same or different, preferably the same. The initiator forms an initiator solution during use, including a first initiator solution and a second initiator solution. The initiators in the first initiator solution and the second initiator solution may be the same or different, preferably the same.

[0013] In this invention, the C1-C4 acrylate is preferably selected from one of methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, and isobutyl acrylate, and more preferably n-butyl acrylate.

[0014] In this invention, the ratio of the mass of C1-C4 acrylate, the mass of acrylic monomers, and the sum of the masses of trimethylolpropane triacrylate and N,N-methylenebisacrylamide can be 145-160:90-110:1, preferably 145-155:90-110:1, more preferably 147-153:95-105:1, and even more preferably 150-152:98-100:1. In some specific embodiments, the C1-C4 acrylate is 71.71 parts by weight, the acrylic monomers are 47.81 parts by weight, and the trimethylolpropane triacrylate and N,N-methylenebisacrylamide together are 0.478 parts by weight. The mass ratio of trimethylolpropane triacrylate to N,N-methylenebisacrylamide can be 1:0.8-1, preferably 1:0.9-1, and even more preferably 1:0.95-1. The present invention has surprisingly discovered that the combined use of trimethylolpropane triacrylate and N,N-methylenebisacrylamide with acrylic monomers and C1-C4 acrylates can help obtain blue hydrogels with both high viscosity and high light transmittance.

[0015] In this invention, the blue hydrogel reaches its maximum viscosity at a pH value of 10 in its viscosity-pH relationship curve.

[0016] The blue hydrogel according to the present invention preferably has a transmittance greater than 70% under visible light at a wavelength λ of 550 nm. The transmittance of the blue hydrogel may vary at different pH values.

[0017] According to a specific embodiment of the present invention, at a pH value of 10, the light transmittance of the blue hydrogel is greater than 87%, preferably greater than 92%, more preferably greater than 95%, and can reach more than 97%.

[0018] According to the blue hydrogel of the present invention, preferably, the viscosity of the blue hydrogel is greater than 8700 mPa•s at a pH value of 10. According to a specific embodiment of the present invention, at a pH value of 10, the viscosity of the blue hydrogel is preferably greater than 9600 mPa•s, more preferably greater than 10000 mPa•s, and can reach 14600 mPa•s.

[0019] In the blue hydrogel of the present invention, preferably, the acrylic monomer is acrylic acid; and the C1-C4 acrylate is n-butyl acrylate.

[0020] On the other hand, the present invention also provides a method for preparing the blue hydrogel as described above, comprising the following steps: 1) A mixture of acrylic monomers, C1-C4 acrylates, trimethylolpropane triacrylate and N,N-methylenebisacrylamide is added to an aqueous solution of the first emulsifier and mixed to obtain a pre-emulsion; 2) At 50–70°C, 5–20 wt% of the pre-emulsion and the first initiator solution are added concurrently to the second emulsifier aqueous solution to react and obtain a seed emulsion; 3) At 50-70°C, the remaining pre-emulsion and the second initiator solution are added in parallel to the seed emulsion in step 2) for reaction. After the reaction is completed, the temperature is lowered to obtain a polyacrylic acid emulsion. 4) The polyacrylic acid emulsion was neutralized with an alkaline solution to a pH value greater than or equal to 7.5 to obtain a blue hydrogel. This yields a blue hydrogel with high viscosity and light transmittance. The inventors are still unclear about the mechanism by which the blue-hued hydrogel is formed.

[0021] Step 1) During mixing, the temperature can be 20–40°C, preferably 25–35°C. The weight ratio of the mixture of acrylic monomers, C1-C4 acrylates, trimethylolpropane triacrylate, and N,N-methylenebisacrylamide to the aqueous solution of the first emulsifier is 115–130:40–45, preferably 118–125:41–43, and more preferably 120–123:42–43. The concentration of the aqueous solution of the first emulsifier can be 3–8 wt%.

[0022] In step 2), the reaction temperature is preferably 55–70°C, more preferably 60–65°C. A portion of the pre-emulsion (5–20 wt%, preferably 10–15 wt%) and the first initiator solution are added concurrently to the second emulsifier aqueous solution for reaction.

[0023] In step 3), the reaction temperature is preferably 55-70°C, more preferably 60-65°C.

[0024] In step 4), the alkaline solution is selected from alkali metal carbonate solutions and alkali metal hydroxide solutions, preferably alkali metal hydroxide solutions. The alkali metal carbonate solution is selected from sodium carbonate solution and / or potassium carbonate solution. The alkali metal hydroxide solution is selected from sodium hydroxide solution and / or potassium hydroxide solution. In this invention, if it is necessary to increase viscosity and light transmittance, the pH value can be adjusted to 8.5-10.

[0025] According to the preparation method of the present invention, preferably, the emulsifiers in the first and second emulsifier aqueous solutions are selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium fatty alcohol polyoxyethylene ether sulfate, and ammonium fatty alcohol polyoxyethylene ether sulfate; the concentration of the first emulsifier aqueous solution is 3-8 wt%; and the concentration of the second emulsifier aqueous solution is 1-5 wt%. This is beneficial for obtaining the blue hydrogel with high viscosity and light transmittance of the present invention.

[0026] In this invention, the emulsifier in the first and second emulsifier aqueous solutions is the same, preferably sodium dodecyl sulfate. The concentration of the first emulsifier aqueous solution is preferably 4-6 wt%, more preferably 4.5-5.5 wt%. The concentration of the second emulsifier aqueous solution is preferably 1.5-4 wt%, more preferably 1.9-3 wt%. The weight ratio of the second emulsifier aqueous solution to the first emulsifier aqueous solution is 58-68:40-45, preferably 59-63:40-43, more preferably 61-63:41-42.

[0027] According to the preparation method of the present invention, preferably, the initiators in the first initiator solution and the second initiator solution are selected from persulfate initiators or persulfate-reducing auxiliary initiator systems, respectively; wherein, the persulfate is selected from ammonium persulfate, potassium persulfate and / or sodium persulfate; the concentrations of the first initiator solution and the second initiator solution are 0.8-1.5 wt% respectively; the mass ratio of the second initiator solution to the first initiator solution is 0.55-0.75:1; the percentage of the sum of the masses of the first initiator solution and the second initiator solution to the sum of the masses of all raw materials in steps 1) to 3) is 0.45-0.8 wt%; wherein, all raw materials in steps 1) to 3) are composed of a first emulsifier aqueous solution, acrylic monomers, C1-C4 acrylates, trimethylolpropane triacrylate, N,N-methylenebisacrylamide, a second emulsifier aqueous solution, a first initiator solution and a second initiator solution.

[0028] In this invention, the initiator in both the first and second initiator solutions is a persulfate, preferably ammonium persulfate. The concentrations of the first and second initiator solutions are the same, preferably 0.9–1.3 wt%, more preferably 1.0–1.1 wt%. The mass ratio of the second initiator solution to the first initiator solution is preferably 0.6–0.7:1. The percentage of the sum of the masses of the first and second initiator solutions relative to the sum of the masses of all raw materials in steps 1) to 3) is preferably 0.5–0.8 wt%, more preferably 0.55–0.75 wt%, even more preferably 0.55–0.7 wt%, and still more preferably 0.6–0.7 wt%.

[0029] According to the preparation method of the present invention, preferably: In step 1), stirring is performed during mixing at a speed of 500–1100 rpm for 30–60 min. In step 2), the reaction is stirred at a speed of 200-500 rpm for 15-35 minutes. In step 3), the remaining pre-emulsion and the second initiator solution are added dropwise to the seed emulsion in a co-current manner for reaction; the dropwise addition time is 1.5 to 3 hours; after the dropwise addition is completed, the reaction is kept at a constant temperature for 50 to 80 minutes; the mixture is stirred during both the dropwise addition and the temperature holding time, and the stirring speed is 200 to 500 rpm. Step 3) also includes: after cooling, filtering through a 100-mesh sieve to obtain a polyacrylic acid emulsion; In step 4), the alkaline solution is a 5–20 wt% alkali metal hydroxide solution. By controlling the stirring speed and dropping time, it is beneficial to obtain a blue hydrogel with high viscosity and light transmittance. Filtering through a sieve yields a uniform polyacrylic acid emulsion. Controlling the alkaline solution and its concentration is beneficial to obtaining a uniform blue hydrogel.

[0030] In this invention, the stirring speed in step 1) is preferably 700-900 rpm, more preferably 750-800 rpm. The stirring time is preferably 35-55 min, more preferably 40-50 min.

[0031] The stirring speed in step 2) is preferably 250–400 rpm, more preferably 300–350 rpm. The stirring time is preferably 20–30 min, more preferably 20–25 min.

[0032] In step 3), the preferred dripping time is 2–2.5 h. The preferred heat preservation reaction time is 60–70 min. The preferred stirring speed is 300–400 rpm.

[0033] In step 4), the alkaline solution is preferably a sodium hydroxide solution with a concentration of 8-15 wt%, for example, 10 wt%.

[0034] Furthermore, the present invention also provides the application of the blue hydrogel prepared according to the above-described method or the preparation method described above as a thickener or suspending agent in daily personal care and cleaning products. These daily personal care and cleaning products include, but are not limited to, shampoos, hand soaps, and shower gels.

[0035] The blue hydrogel of this invention exhibits high viscosity and light transmittance, displaying its blue hue without the addition of additional pigments. Its viscosity and light transmittance vary at different pH values ​​and can be adjusted according to actual needs. This blue hydrogel can be used as a thickener or suspending agent in daily washing and cleaning products. Because the hydrogel itself has a beautiful blue color, it helps to cover impurities in raw materials, resulting in a more uniform color in the finished product, thus reducing formulation costs and the amount of additional pigments needed. During production, since the thickener or suspending agent is inherently colored, clumping and undissolved portions can be directly observed during stirring, aiding in the judgment of dissolution and dispersion states and improving production convenience. The preparation method of this invention yields a blue hydrogel with both high viscosity and light transmittance. The preparation conditions of this invention are mild, which is conducive to its widespread application. Attached Figure Description

[0036] Figure 1 This is a physical image of the polyacrylic acid emulsion obtained in Example 1 of the present invention.

[0037] Figure 2 This is a photograph of the blue hydrogel obtained in Example 1 of the present invention.

[0038] Figure 3 The graph shows the relationship between viscosity and amount of ammonium persulfate solution used in Examples 1, 2 to 4 and Comparative Example 1 of the present invention.

[0039] Figure 4 The graph shows the relationship between transmittance and the amount of ammonium persulfate solution used in Examples 1, 2 to 4 and Comparative Example 1 of the present invention.

[0040] Figure 5 The viscosity-pH value relationship curves of the blue hydrogels obtained in Examples 1 to 8 of the present invention are shown.

[0041] Figure 6 Transmittance-pH value relationship curves of the blue hydrogels obtained in Examples 1 to 8 of the present invention. Detailed Implementation

[0042] The testing method is described below: (1) Viscosity test The instrument used was a Brookfield DV2TRVTJ0 dial viscometer from the USA.

[0043] The obtained hydrogel sample was placed in a constant temperature chamber at 25°C for 4 hours, and then the viscosity was tested with a viscometer at 50 rpm using rotor No. 6.

[0044] (2) Transmittance test A Shimadzu UV-1900i UV-Vis spectrophotometer (Suzhou) Co., Ltd. was used. Before measuring the hydrogel samples, water was used as a blank reference for zeroing. Then, the light transmittance of the hydrogel at λ=550 nm was measured on the spectrophotometer. The sample was tested three times, and the average value was taken.

[0045] (3) Determination of the particle size of polyacrylic acid emulsion: Malvern Zetasizer Nano ZS (Malvern nanoparticle size and Zeta potential analyzer) was used.

[0046] The following describes the sources of some raw materials: n-Butyl acrylate (BA): Purchased from Maclean's, lot number B801799.

[0047] Acrylic acid (MAA): Purchased from Maclean's, lot number M812916.

[0048] Trimethylolpropane triacrylate (TMPTA): Purchased from Maclean's, lot number T834479.

[0049] N,N-Methylenebisacrylamide: Purchased from Aladdin, batch number M104022.

[0050] In the following examples, Comparative Example 1, and Investigational Example, the total mass percentage of ammonium persulfate solution = (total mass of ammonium persulfate solution / (sum of the masses of all raw materials in steps 1) to 3)) × 100%. All raw materials in steps 1) to 3) consist of an aqueous solution of the first emulsifier, n-butyl acrylate, acrylic acid, trimethylolpropane triacrylate, N,N-methylenebisacrylamide, an aqueous solution of the second emulsifier, a first initiator solution, and a second initiator solution. In Comparative Examples 2 to 5, adjustments were made according to the different raw materials.

[0051] Example 1 1) Preparation of preemulsion Two parts by weight of sodium dodecyl sulfate (SDS) were mixed with 40 parts by weight of deionized water and stirred thoroughly at 35°C until dissolved to obtain an aqueous solution of the first emulsifier.

[0052] A mixture of n-butyl acrylate (BA), acrylic acid (MAA), trimethylolpropane triacrylate (TMPTA), and N,N-methylenebisacrylamide (120 parts by weight) was added dropwise to an aqueous solution of the first emulsifier and stirred at 800 rpm for 40 minutes to obtain a uniform white pre-emulsion. The mass ratio of n-butyl acrylate (BA), the mass of acrylic acid (MAA), and the sum of the masses of trimethylolpropane triacrylate (TMPTA) and N,N-methylenebisacrylamide in the mixture was 150:100:1, and the mass ratio of TMPTA to N,N-methylenebisacrylamide was 1:1.

[0053] 2) Preparation of seed emulsion Mix 1.2 parts by weight of SDS with 60 parts by weight of deionized water and stir thoroughly until completely dissolved to obtain a second emulsifier aqueous solution.

[0054] The aqueous solution of the second emulsifier was heated to 65°C, and a small portion of the pre-emulsion (10 wt% of the pre-emulsion prepared above) and 1.0 part by weight of ammonium persulfate (APS) solution (i.e. the first initiator solution with a concentration of 1 wt%) were added dropwise to the aqueous solution of the second emulsifier while stirring at 300 rpm. After the addition was completed, the reaction was stirred for 20 min. During this process, the emulsion gradually turned blue, and the seed emulsion was obtained.

[0055] 3) Semi-continuous seed emulsion polymerization The seed emulsion was maintained at 65°C. The remaining pre-emulsion was placed in a 35°C water bath and continuously stirred at 800 rpm. The remaining emulsion was added dropwise to the seed emulsion using a peristaltic pump, while simultaneously adding 0.6 parts by weight of ammonium persulfate solution (i.e., the second initiator solution, concentration 1 wt%) to the seed emulsion through a constant pressure feeding funnel. During the reaction, the stirring speed was 300 rpm. The dropping time was controlled to be 2.5 h. After the dropping was completed, the mixture was kept at 65°C for another 1 h. After the reaction was completed, the mixture was cooled to room temperature, and the reaction system was filtered through a 100-mesh sieve to obtain a polyacrylic acid emulsion.

[0056] 4) Dilute the 20 mL of polyacrylic acid emulsion obtained in step 3) with 80 mL of distilled water to obtain a diluted polyacrylic acid emulsion. Then adjust the pH of the diluted polyacrylic acid emulsion to 10 with a prepared 10 wt% sodium hydroxide solution to obtain a blue hydrogel.

[0057] In this embodiment, the total mass percentage of the ammonium persulfate solution is 0.7 wt%.

[0058] See the physical image of the obtained polyacrylic acid emulsion. Figure 1 .Depend on Figure 1It can be seen that the obtained polyacrylic acid emulsion is mainly a milky white system, with a uniform light blue hue on the basis of the inherent milky white base color of the polymer resin. No additional color pigments were added, the emulsion was uniformly dispersed, and there was no sediment or scum.

[0059] The obtained polyacrylic acid emulsion has a solid content of approximately 40±2wt%, a pH value of 1.98, a viscosity of 46.4 mPa•s (using the above-mentioned viscometer, rotor No. 2, 100 rpm), and an emulsion particle size of 50–80 nm.

[0060] See the image of the resulting blue hydrogel. Figure 2 The resulting blue hydrogel had a solute concentration of approximately 5 wt%. Figure 2 The black background color affects the observation of the transparency of the blue hydrogel, which is actually transparent. The viscosity and transmittance of the obtained blue hydrogel were tested; the viscosity was 14600 mPa•s, and the transmittance was 97.95%.

[0061] Example 2 The only difference from Example 1 is that the total amount of ammonium persulfate solution used is 1.1 parts by weight (0.5 wt%). The resulting blue hydrogel has a viscosity of 9680 mPa•s and a transmittance of 92.47%.

[0062] Example 3 The only difference from Example 1 is that the total amount of ammonium persulfate solution used is 1.35 parts by weight (0.6 wt%). The resulting blue hydrogel has a viscosity of 10800 mPa•s and a transmittance of 92.90%.

[0063] Example 4 The only difference from Example 1 is that the total amount of ammonium persulfate solution used is 1.8 parts by weight (0.8 wt%). The resulting blue hydrogel has a viscosity of 8790 mPa•s and a transmittance of 95.72%.

[0064] Comparative Example 1 The only difference from Example 1 is that the total amount of ammonium persulfate solution used is 0.9 parts by weight (0.4 wt%). The resulting blue hydrogel has a viscosity of 6920 mPa•s and a transmittance of 71.29%.

[0065] The viscosity and transmittance of the blue hydrogels obtained in Examples 1 to 4 and Comparative Example 1 were plotted as curves, and the results are shown in the figure. Figure 3 and Figure 4 .

[0066] Depend on Figure 3It can be seen that when the total mass percentage of ammonium persulfate solution is in the range of 0.4%–0.7 wt%, the viscosity of the resulting blue hydrogel gradually increases with the increase of the amount of ammonium persulfate solution. The viscosity is highest at a total mass percentage of 0.7 wt%, reaching 14600 mPa•s. However, when the total mass percentage of ammonium persulfate solution is in the range of 0.7%–0.8 wt%, the viscosity of the resulting blue hydrogel decreases with further increases in the amount of ammonium persulfate solution.

[0067] Depend on Figure 4 It is observed that when the total mass percentage of ammonium persulfate solution is in the range of 0.4–0.7 wt%, the transmittance of the blue hydrogel increases with increasing ammonium persulfate solution concentration. The transmittance is highest at 0.7 wt%, reaching 97.95%. However, when the total mass percentage of ammonium persulfate solution is in the range of 0.7–0.8 wt%, the transmittance decreases with increasing ammonium persulfate solution concentration. At 0.8 wt%, the transmittance is still relatively high at 95.72%, but the viscosity decreases significantly. Considering all factors, the preferred total mass percentage of ammonium persulfate solution is 0.5–0.7 wt%, more preferably 0.6–0.7 wt%.

[0068] Comparative Example 2 The only difference from Example 1 was the addition of 0.62 parts by weight of N-vinylpyrrolidone to the mixture, bringing the total weight of the mixture to 120.62 g. The total mass percentage of the ammonium persulfate solution remained unchanged. A blue hydrogel with a viscosity of 6200 mPa•s and a transmittance of 82% was obtained.

[0069] Comparative Example 3 The only difference from Example 1 was the addition of 0.12 parts by weight of AMPS (2-acrylamido-2-methylpropanesulfonic acid) to the mixture, bringing the total weight of the mixture to 120.12 g. The total mass percentage of the ammonium persulfate solution remained unchanged. A blue hydrogel with a viscosity of 8600 mPa•s and a transmittance of 94.62% was obtained.

[0070] Comparing Comparative Example 2, Comparative Example 3 and Example 1, it can be seen that the blue hydrogel obtained in Example 1 has significantly higher viscosity and light transmittance.

[0071] Comparative Example 4 The only difference from Example 1 was the absence of trimethylolpropane triacrylate. No blue hydrogel was obtained. After adjusting the pH of the diluted polyacrylic acid emulsion to 10, the resulting gel had a low viscosity, less than 6500 mPa•s.

[0072] Comparative Example 5 The only difference from Example 1 was the absence of N,N-methylenebisacrylamide. No blue hydrogel was obtained. After adjusting the pH of the diluted polyacrylic acid emulsion to 10, the resulting gel had a low viscosity, less than 7500 mPa•s.

[0073] The present invention also investigated the viscosity and transmittance of the blue hydrogels obtained at different pH values. See Examples 1 to 8 below for details.

[0074] Example 1 1) Preparation of preemulsion Two parts by weight of sodium dodecyl sulfate (SDS) were mixed with 40 parts by weight of deionized water and stirred thoroughly at 35°C until dissolved to obtain an aqueous solution of the first emulsifier.

[0075] A mixture of n-butyl acrylate (BA), acrylic acid (MAA), trimethylolpropane triacrylate (TMPTA), and N,N-methylenebisacrylamide (120 parts by weight) was added dropwise to an aqueous solution of the first emulsifier and stirred at 800 rpm for 40 minutes to obtain a uniform white pre-emulsion. The mass ratio of n-butyl acrylate (BA), acrylic acid (MAA), and the sum of the masses of trimethylolpropane triacrylate (TMPTA) and N,N-methylenebisacrylamide in the mixture was 160:100:1, and the mass ratio of TMPTA to N,N-methylenebisacrylamide was 1:1.

[0076] 2) Preparation of seed emulsion Mix 1.2 parts by weight of SDS with 60 parts by weight of deionized water and stir thoroughly until completely dissolved to obtain a second emulsifier aqueous solution.

[0077] The aqueous solution of the second emulsifier was heated to 65°C, and a small portion of the pre-emulsion (10 wt% of the pre-emulsion prepared above) and 1.0 part by weight of ammonium persulfate (APS) solution (i.e. the first initiator solution with a concentration of 1 wt%) were added dropwise to the aqueous solution of the second emulsifier in parallel at a stirring speed of 300 rpm. After the addition was completed, the reaction was stirred for 20 min. During this process, the emulsion gradually turned blue, and the seed emulsion was obtained.

[0078] 3) Semi-continuous seed emulsion polymerization The seed emulsion was maintained at 65°C. The remaining pre-emulsion was placed in a 35°C water bath and continuously stirred at 800 rpm. The remaining emulsion was added dropwise to the seed emulsion using a peristaltic pump, while simultaneously adding 0.6 parts by weight of ammonium persulfate solution (i.e., the second initiator solution, concentration 1 wt%) to the seed emulsion through a constant pressure feeding funnel. During the reaction, the stirring speed was 300 rpm. The dropping time was controlled to be 2.5 h. After the dropping was completed, the mixture was kept at 65°C for another 1 h. After the reaction was completed, the mixture was cooled to room temperature, and the reaction system was filtered through a 100-mesh sieve to obtain a polyacrylic acid emulsion.

[0079] 4) Dilute the 20 mL of polyacrylic acid emulsion obtained in step 3) with 80 mL of distilled water to obtain a diluted polyacrylic acid emulsion. Then adjust the pH of the diluted polyacrylic acid emulsion to 7.5 with a prepared 10 wt% sodium hydroxide solution to obtain a blue hydrogel.

[0080] The viscosity and transmittance of the resulting blue hydrogel were tested. The viscosity was 1450 mPa•s and the transmittance was 72.95%.

[0081] Examining Example 2 The only difference from Example 1 is that the pH of the diluted polyacrylic acid emulsion was adjusted to 8.0 to obtain a blue hydrogel. The viscosity and transmittance of the obtained blue hydrogel were tested; the viscosity was 4700 mPa•s, and the transmittance was 82.41%.

[0082] Examining Example 3 The only difference from Example 1 is that the pH of the diluted polyacrylic acid emulsion was adjusted to 8.5 to obtain a blue hydrogel. The viscosity and transmittance of the obtained blue hydrogel were tested, and the viscosity was 7860 mPa•s, and the transmittance was 86.90%.

[0083] Example 4 The only difference from Example 1 is that the pH of the diluted polyacrylic acid emulsion was adjusted to 9.0 to obtain a blue hydrogel. The viscosity and transmittance of the obtained blue hydrogel were tested; the viscosity was 9920 mPa•s, and the transmittance was 87.90%.

[0084] Examining Example 5 The only difference from Example 1 is that the pH of the diluted polyacrylic acid emulsion was adjusted to 9.5 to obtain a blue hydrogel. The viscosity and transmittance of the obtained blue hydrogel were tested; the viscosity was 10780 mPa•s, and the transmittance was 88.10%.

[0085] Examining Example 6 The only difference from Example 1 is that the pH of the diluted polyacrylic acid emulsion was adjusted to 10 to obtain a blue hydrogel. The viscosity and transmittance of the obtained blue hydrogel were tested; the viscosity was 11700 mPa•s, and the transmittance was 88.10%.

[0086] Examine Example 7 The only difference from Example 1 is that the pH of the diluted polyacrylic acid emulsion was adjusted to 10.5 to obtain a blue hydrogel. The viscosity and transmittance of the obtained blue hydrogel were tested; the viscosity was 10240 mPa•s, and the transmittance was 87.70%.

[0087] Examine Example 8 The only difference from Example 1 is that the pH of the diluted polyacrylic acid emulsion was adjusted to 11.0 to obtain a blue hydrogel. The viscosity of the obtained blue hydrogel was tested, and it was 9280 mPa•s with a transmittance of 86.60%.

[0088] Table 1 project Example 1 Example 2 Examining Example 3 Examining Example 4 Examining Example 5 Examining Example 6 Examine Example 7 Examine Example 8 pH value 7.5 8.0 8.5 9.0 9.5 10.0 10.5 11.0 Viscosity 1450 4700 7860 9920 10780 11700 10240 9280 Light transmittance 72.95 82.41 86.90 87.90 88.10 88.10 87.70 86.60 Note: In the table, viscosity is in mPa•s and transmittance is in %.

[0089] The viscosity-pH curves of the blue hydrogels obtained in Examples 1 to 8 are shown below. Figure 5 The transmittance-pH value curve is shown below. Figure 6 .

[0090] From Table 1 and Figure 5 It can be seen that the viscosity of the blue hydrogel obtained by this invention gradually increases with increasing pH value in the pH range of 7.5 to 10, reaching its maximum at pH value of 10. In the pH range of 10 to 11, the viscosity gradually decreases with increasing pH value.

[0091] From Table 1 and Figure 6 It can be seen that the transmittance of the blue hydrogel obtained in this invention increases with increasing pH value within the range of 7.5 to 9.5. Specifically, the increase in transmittance is significant within the pH range of 7.5 to 8.5. Within the pH range of 8.5 to 9.5, the increase in transmittance with increasing pH value is not significant. The transmittance reaches its maximum at pH 9.5. Within the pH range of 9.5 to 11.0, the transmittance gradually decreases with increasing pH value.

[0092] This invention is not limited to the above-described embodiments. Any modifications, improvements, or substitutions that can be conceived by those skilled in the art without departing from the essential content of this invention fall within the scope of this invention.

Claims

1. A blue hydrogel, characterized in that, Without any added pigments, the light transmittance is greater than 70%, and the appearance is transparent or semi-transparent. In its viscosity-pH value relationship curve, in the pH value range of 7.5 to 10, the viscosity gradually increases with the increase of pH value, and in the pH value range of 10 to 11, the viscosity gradually decreases with the increase of pH value. It is prepared from raw materials including: acrylic monomers, C1-C4 acrylates, trimethylolpropane triacrylate and N,N-methylenebisacrylamide; The mass ratio of the C1-C4 acrylate, the mass of the acrylic monomer, and the sum of the masses of trimethylolpropane triacrylate and N,N-methylenebisacrylamide is 145-160:90-110:1; the mass ratio of trimethylolpropane triacrylate to N,N-methylenebisacrylamide is 1:0.8-1. Wherein, the acrylic monomer is selected from one or more of acrylic acid and methacrylic acid; the C1-C4 acrylate is selected from one or more of methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate and tert-butyl acrylate.

2. The blue hydrogel according to claim 1, characterized in that, Under visible light at a wavelength of 550 nm, the transmittance of the blue hydrogel is greater than 70%.

3. The blue hydrogel according to claim 1, characterized in that, At pH 10, the viscosity of the blue hydrogel is greater than 8700 mPa•s.

4. The blue hydrogel according to claim 1, characterized in that, The acrylic monomer is acrylic acid; the C1-C4 acrylate is n-butyl acrylate.

5. A method for preparing a blue hydrogel as described in any one of claims 1 to 4, characterized in that, Includes the following steps: 1) A mixture of acrylic monomers, C1-C4 acrylates, trimethylolpropane triacrylate and N,N-methylenebisacrylamide is added to an aqueous solution of the first emulsifier and mixed to obtain a pre-emulsion; 2) At 50–70°C, 5–20 wt% of the pre-emulsion and the first initiator solution are added concurrently to the second emulsifier aqueous solution to react and obtain a seed emulsion; 3) At 50-70°C, the remaining pre-emulsion and the second initiator solution are added to the seed emulsion in parallel flow for reaction. After the reaction is completed, the temperature is lowered to obtain a polyacrylic acid emulsion. 4) Neutralize the polyacrylic acid emulsion with an alkaline solution to a pH value greater than or equal to 7.5 to obtain a blue hydrogel.

6. The preparation method according to claim 5, characterized in that, The emulsifiers in the first and second emulsifier aqueous solutions are selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium fatty alcohol polyoxyethylene ether sulfate, and ammonium fatty alcohol polyoxyethylene ether sulfate, respectively; the concentration of the first emulsifier aqueous solution is 3-8 wt%; and the concentration of the second emulsifier aqueous solution is 1-5 wt%.

7. The preparation method according to claim 5, characterized in that, The initiators in the first initiator solution and the second initiator solution are respectively selected from persulfate initiators or persulfate-reducing auxiliary initiator systems; wherein, the persulfate is selected from ammonium persulfate, potassium persulfate and / or sodium persulfate.

8. The preparation method according to claim 5, characterized in that, The concentrations of the first initiator solution and the second initiator solution are 0.8–1.5 wt% respectively; the mass ratio of the second initiator solution to the first initiator solution is 0.55–0.75:1; the sum of the masses of the first initiator solution and the second initiator solution accounts for 0.45–0.8 wt% of the sum of the masses of all raw materials in steps 1) to 3). All raw materials in steps 1) to 3) consist of an aqueous solution of the first emulsifier, acrylic monomers, C1-C4 acrylates, trimethylolpropane triacrylate, N,N-methylenebisacrylamide, an aqueous solution of the second emulsifier, the first initiator solution, and the second initiator solution.

9. The preparation method according to claim 5, characterized in that: In step 1), stirring is performed during mixing at a speed of 500–1100 rpm for 30–60 min. In step 2), the reaction is stirred at a speed of 200-500 rpm for 15-35 minutes. In step 3), the remaining pre-emulsion and the second initiator solution are added dropwise to the seed emulsion in a co-current manner for reaction; the dropwise addition time is 1.5 to 3 hours; after the dropwise addition is completed, the reaction is kept at a constant temperature for 50 to 80 minutes; the mixture is stirred during both the dropwise addition and the temperature holding time, and the stirring speed is 200 to 500 rpm. Step 3) also includes: after cooling, filtering through a 100-mesh sieve to obtain a polyacrylic acid emulsion; In step 4), the alkaline solution is a 5-20 wt% alkali metal hydroxide solution.

10. The use of the blue hydrogel according to any one of claims 1 to 4 or the blue hydrogel prepared by the preparation method according to any one of claims 5 to 9 as a thickener or suspending agent in daily washing and cleaning products.